The Struggle Of Antonia Shimerda And Lena Lingard Against Patriarchal Gender Roles Portrayed In Willa Cather’s My Antonia - Kinanti Resmi Hayati; Laksmi Budiana (Universitas Muhammadiyah Surabaya, 2019)
Women is never ending issue to discuss. My Antonia is one of popular novel in early 20th century which is told about women’s struggle. There are not many novels or literary works that discuss about woman’s struggle against patriarchal gender role explicitly such as in My Antonia by Willa Cather. This topic will discuss about the struggle of Antonia Shimerda and Lena Lingard against patriarchal gender role. As already known, equality is very difficult to get for women in early 20th century. The phenomenon of inequality between men and women is being a trigger for women movement or usually called as feminist. The issue of inequality attracts women to start their movement against the patriarchal gender role which has been already existed in the society since a long time ago. Antonia Shimerda and Lena Lingard depicted in the novel as woman who decided to focus with their career rather than to get married. It is still taboo for woman to behave as feminist in that era.Key words: patriarchal gender roles, struggle, equality, feminist.